2017
DOI: 10.1111/1748-8583.12148
|View full text |Cite
|
Sign up to set email alerts
|

High‐performance work systems and creativity implementation: the role of psychological capital and psychological safety

Abstract: Unimplemented creative ideas are potentially wasted opportunities for organisations. Although it is largely understood how to encourage creativity among employees, how to ensure this creativity is implemented remains underexplored. The objective of the current study is to identify the underlying mechanisms that explain the relationship between high‐performance work systems and creativity implementation. Drawing from the job demands–resources model, we explore a model of psychological capital and psychological … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
132
0
6

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 133 publications
(177 citation statements)
references
References 107 publications
9
132
0
6
Order By: Relevance
“…The COR theory states that the loss or potential loss of resources is psychologically threatening [59]. HRM practice plays an important role in building employees' psychological safety because employees are particularly concerned about HR decisions [60]. Previous research has shown that psychological safety is a function of interpersonal factors such as trustworthy relationships and predictable leadership behaviors.…”
Section: Hypothesis Developmentmentioning
confidence: 99%
“…The COR theory states that the loss or potential loss of resources is psychologically threatening [59]. HRM practice plays an important role in building employees' psychological safety because employees are particularly concerned about HR decisions [60]. Previous research has shown that psychological safety is a function of interpersonal factors such as trustworthy relationships and predictable leadership behaviors.…”
Section: Hypothesis Developmentmentioning
confidence: 99%
“…For example, Heffernan and Dundon (2016) argue that HR practices can have a signaling effect on employees by increasing their feelings of value and worth. Furthermore, HPWS can provide more psychological resources and help employees better deal with job demands (Agarwal and Farndale, 2017), which in turn elicit employees' sense of organizational support and engender their well-being attributions.…”
Section: Employee-perceived High-performance Work Systems Commitmentmentioning
confidence: 99%
“…Psychological capital is a kind of value-added capital bringing benefits to individuals. This positive state of mind helps individuals to be optimistic and develop their own abilities (Agarwal & Farndale, 2017). Studies have shown that the improvement of psychological capital can enable people to maintain positive attitudes, beliefs, hopes and confidence, and encourage individuals to accumulate energy at work and improve their individual perception (O"Donohue, Martin, & Torugsa, 2015).…”
Section: Mechanism Of the Psychological Capital On The Ability Of Empmentioning
confidence: 99%